Pemenuhan Hak Anak Pasca Perceraian Perspektif Hukum Positif dan Teori Tujuan Hukum Gustav Radbruch - Kanifah, Anisa Nur; Santoso, Lukman (Al-Syakhsiyyah: Journal of Law and Family Studies, 2024)
This research began with the problem of providing children with post-divorce rights which were not fulfilled by both parents. The aim of this research is to see the extent to which children's rights after divorce are implemented. This research is a type of qualitative field research. The approach used is normative juridical with a type of clinical research. The findings of this research show that explaining children's rights after divorce in Bekiring Village, Pulung District, Ponorogo Regency from a positive legal perspective, of the 6 (six) residents who were used as informants in the parenting aspect, two informants were in compliance while the other four were not. The aspect of paying for a living (father) has been fulfilled by the father with all his efforts, but one informant enjoys the living carried out by the mother. Aspects of caring for children who are not mumayyiz yet with their mother, one is suitable while the other five are in the care of the father. Furthermore, the implementation of positive law regarding the granting of children's rights after divorce in Bekiring Village, Pulung District, Ponorogo Regency, from the perspective of Gustav Radbruch's theory of legal objectives, in the aspect of legal justice regarding children who have the right to choose to live with their father/mother has not been implemented. In the aspect of legal benefits, some of it has been implemented, but regarding the care of children who are not yet mumayyiz, it has not been implemented well. While the aspect of legal certainty has not been implemented well, the value of certainty in obtaining support from the father has been implemented.